Application of the SmartLB Load Balancer to Runtime and Power Consumption Reduction of Applications in Parallel Environments - dos Santos, Vinicius R. S.; Padoin, Edson L.; Navaux, Philippe O. A. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
This paper presents a proposal of a new load balancer which aims reduce the runtime and power consumption of parallel applications when these are runned in shared memory environments. The algorithm of the balancer collects system and application information in real time and then use it to make task migration decisions. For the implementation of strategy was used the Charm++ parallel programming. Preliminary results show reductions of up to 35.36% of runtime and energy consumption for three benchmarks used in the tests.